2011
DOI: 10.1016/j.bpj.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Ensemble Modeling of Intrinsically Disordered Proteins: p53 N-Terminal Domain

Abstract: Intrinsically disordered proteins (IDPs) are ubiquitous and play key roles in transcriptional regulations and other cellular processes. To characterize diverse structural ensembles of IDPs, combinations of NMR and computational modeling showed some promise, but they need further improvements. Here, for accurate and efficient modeling of IDPs, we propose a systematic multiscale computational method. We first perform all-atom replica-exchange molecular dynamics (MD) simulations of a few fragments selected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 51 publications
4
93
0
2
Order By: Relevance
“…These results motivated us to make the domain III-IV linker region flexible (38). The flexible linker is further justified by the following arguments: (i) When we constructed the E. coli DnaA domain III-IV homology model, the secondary structure prediction of the I-TASSER modeling server suggests that the linker tends to form loops rather than an α-helix (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results motivated us to make the domain III-IV linker region flexible (38). The flexible linker is further justified by the following arguments: (i) When we constructed the E. coli DnaA domain III-IV homology model, the secondary structure prediction of the I-TASSER modeling server suggests that the linker tends to form loops rather than an α-helix (37).…”
Section: Resultsmentioning
confidence: 99%
“…First, we used a flexible linker model (38) for the linker between domains III and IV. The flexibility could be somewhat overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Such effect of phosphorylation on the intrinsic propensity toward certain local backbone conformations can be especially important for intrinsically disordered proteins, for which the long-range global interactions are less significant compared to those of well-structured proteins. In addition, the intrinsic propensity toward certain local backbone conformations of a certain amino acid is also an important input for some computational models of protein folding/aggregation and structure predictions [11][12][13][14][15][16][17]. For example, recent computational works showed that introducing amino acid-specific parameters to the intrinsic conformational propensity in the all-atom force field can drastically improve protein folding and structure predictions [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Last in this chapter, we note that the coarse-grained model is also useful to rationally explain coupled folding and binding, as done by Okazaki and Takada [45], and Terakawa and Takada [56]. Recently, Matsushita and Kikuchi [37] have proposed a novel picture for intrinsic disorder, where structural frustrations are designed for inducing the intrinsic disorder.…”
Section: Coupled Folding and Bindingmentioning
confidence: 91%